2023
DOI: 10.1186/s12873-023-00885-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study on clinical and epidemiological profile of adult patients presenting to the emergency department with suspected upper gastrointestinal bleed

Alok Raj,
Nidhi Kaeley,
Hari Prasad
et al.

Abstract: Background and objective Bleeding from the upper gastrointestinal (GI) tract is one of the common medical emergencies. In this study, we assessed patients’ socio-demographic and clinical characteristics and the association of clinical characteristics with treatment outcomes among patients with suspected upper gastrointestinal bleed (UGIB) presenting to the emergency department (ED). At present, there is a scarcity of data on UGIB in Northern part of India. Materia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…1,7 Elevated mortality rates, recurrent bleeding episodes, and the necessity for endoscopic hemostasis or surgical intervention are linked to risk factors such as being over the age of 60 and having comorbidities. 8 An analysis revealed that the presence of comorbidities such as DM or metastatic malignancy, as well as hypotension during hospitalization, are significant predictors of short-term mortality. 9 Particularly in diabetic patients, diabetic angiopathy compromises mucosal integrity, resulting in more severe ulcers, and DM heightens susceptibility to acute gastrointestinal injury while impacting mucosal healing.…”
Section: Original Articlementioning
confidence: 99%
“…1,7 Elevated mortality rates, recurrent bleeding episodes, and the necessity for endoscopic hemostasis or surgical intervention are linked to risk factors such as being over the age of 60 and having comorbidities. 8 An analysis revealed that the presence of comorbidities such as DM or metastatic malignancy, as well as hypotension during hospitalization, are significant predictors of short-term mortality. 9 Particularly in diabetic patients, diabetic angiopathy compromises mucosal integrity, resulting in more severe ulcers, and DM heightens susceptibility to acute gastrointestinal injury while impacting mucosal healing.…”
Section: Original Articlementioning
confidence: 99%